Analysis of The Application of Ecotourism Principles In Indonesian Natural Tourism Destinations: A Literature Review - Mokodongan, Trisagia (Journal of Indonesian Tourism, Hospitality and Recreation, 2024)
ABSTRACTEcotourism proliferates in many countries worldwide and is considered an attractive solution to meet the needs of the environment and tourism development. Ecotourism development faces various challenges and maintains consistent application of ecotourism principles. Therefore, this paper seeks to analyse the application of ecotourism principles in natural tourism destinations in Indonesia. The principles studied in this paper are the element of conservation, the element of local community involvement, and the element of interpretation according to the definition of The International Ecotourism Society. This paper uses the literature review method to explore data. The literature search database used is Google Scholar. The results showed that not all ecotourism destinations apply the principles of ecotourism. All ecotourism destinations utilise natural and cultural resources. The principle of conservation that is maintained is only found in national parks. Interpretation is the principle that is most often not applied in ecotourism destinations.ABSTRAKEkowisata berkembang di banyak negara di seluruh dunia dan dianggap sebagai solusi yang menarik untuk memenuhi kebutuhan lingkungan dan pengembangan pariwisata. Pengembangan ekowisata menghadapi berbagai tantangan untuk mempertahankan penerapan prinsip-prinsip ekowisata secara konsisten. Oleh karena itu, tulisan ini berusaha menganalisis penerapan prinsip-prinsip ekowisata di destinasi wisata alam di Indonesia. Prinsip-prinsip yang dikaji dalam tulisan ini adalah unsur konservasi, unsur pelibatan masyarakat lokal, dan unsur interpretasi sesuai dengan definisi The International Ecotourism Society. Artikel ini menggunakan metode tinjauan literatur untuk menggali data. Basis data pencarian literatur yang digunakan adalah Google Scholar. Hasil penelitian menunjukkan bahwa tidak semua destinasi ekowisata menerapkan prinsip-prinsip ekowisata. Semua destinasi ekowisata memanfaatkan sumber daya alam dan budaya. Prinsip konservasi yang dipertahankan hanya terdapat pada taman nasional. Interpretasi merupakan prinsip yang paling sering tidak diterapkan di destinasi ekowisata.